Implementation of Interpretation Method in Memorizing Al-Quran at Darul Huffadz Islamic Boarding School Rembang Purbalingga (Study Performance of Al Qur’an by Ingrid Mattson) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
The tradition of memorizing the Qur’an has long been carried out in various regions of the archipelago. The effort to memorize the Qur’an was originally carried out by scholars who studied in the Middle East through their teachers. However, in subsequent developments, the tendency to memorize the Qur’an began to be of great interest to the Indonesian people. Darul Huffadz Tahfidzul Qur'an Islamic Boarding School is one of the boarding schools that has a program for memorizing the Qur’an or also called tahfizh al-Qur'an. This cottage has many activities like other tahfidz Islamic boarding schools. According to Ingrid Mattson, learning the Qur’an should encourage the formation of good character, strong ethics, an understanding of social justice, and continuous self-improvement. Ingrid Mattson is an American Islamic scholar known for her contributions to the study of the Qur’an and the understanding of Islam. Ingrid Mattson's thoughts on learning the Qur’an emphasize the importance of a holistic approach, practical goals, and contextual understanding. He argues that the Qur’an is not only a holy text that must be studied academically, but also as a guide that provides moral and ethical guidance to individuals and society.